ABSORPSI KARBONDIOKSIDA MENGGUNAKAN CAUSTIC SODA SEBAGAI ABSORBEN - Nida Sopiah; Susi Sulistia; Dwindrata B Aviantara; Adi Mulyanto (Pusat Standardisasi Instrumen Kualitas Lingkungan Hidup Laboratorium Lingkungan (P3KLL), 2009)
The increase of atmospheric CO2 gas can cause the increasing of earth’s surface temperature. This is one ofphenomena that ensues as global warming. Global warming occurred because of excess greenhouse effects (morethan normal conditions) of the atmosphere as the result of the disturbance of green house gases composition suchas CO2 (carbon dioxide), CH4 (methane), and N2O (nitrous oxide). Caustic soda can be used as an absorbent toabsorb carbon dioxide. A series of vessels that contained caustic soda solution able to absorb carbon dioxideoriginating from heated acidic calcium carbonate. From the study it was found that vessel-1 capable of absorbing75.6% and vessel-2 24.4% of the released carbon dioxide.